Integrating Sedekah Context in Mathematics Learning to Enhance Students' Mathematical Communication Skills and Awareness of SDG 1: No-Poverty - Nurniqta; Johar, Rahmah; Anwar; Ishak, Muhammad Izzuddin Syakir; Oktavia, Rini (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
The implementation of Education for Sustainable Development (ESD) requires students to have higher order thinking skills (HOTs), which remain challenging for many Indonesian students. One key component of HOT is mathematical communication skills, which can be improved through the Problem-Based Learning (PBL) model. From an Islamic perspective, Sedekah (Sedekah) represents an act of giving that aligns with the Sustainable Development Goal (SDG) 1 objective of poverty alleviation. This study aims to determine the differences in enhancing mathematical communication skills and students' awareness of No-Poverty through PBL learning in the context of Sedekah in Islamic and Regular Schools. This study employed a quantitative approach and a quasi-experimental research design. The population was all students in one Regular School, Banda Aceh and one Islamic School, Aceh Besar, Aceh, Indonesia. This sample included 56 students in an experimental class and 56 in a control class. The instruments in this study were a mathematical communication skill test and a questionnaire assessing students' awareness of No-Poverty. The hypothesis was tested using MANOVA, the Independent t-test, and the two-way ANOVA. The effect size of PBL learning was determined based on the Cohen-d effect size calculation. The findings reveal a significant difference in the improvement of mathematical communication skills and awareness of poverty alleviation between students in regular and Islamic schools. However, no interaction was found between the PBL model contextualized in sedekah and students' educational levels regarding mathematical communication skills and awareness of poverty alleviation. These results suggest that the PBL model effectively enhances students' mathematical communication skills and awareness of poverty alleviation.